(untitled) (Journal of the College of Basic Education, 2026)
This research paper investigates the impact of modern teaching methods on enhancing the pedagogical skills of English language teachers. As education evolves to meet the needs of 21st-century learners, it is imperative for teaching strategies to adapt accordingly. The study explores a variety of modern teaching approaches—including Communicative Language Teaching, Task-Based Learning, the Flipped Classroom, Project-Based Learning, and Technology-Integrated Instruction—and evaluates their effectiveness in improving classroom dynamics, teacher performance, and student outcomes. Drawing from established learning theories and recent educational research, the paper highlights how these methods empower teachers to become facilitators of learning, integrate digital tools effectively, and foster a learner-centered environment. The findings suggest that while these approaches offer substantial benefits, their successful implementation requires professional development, institutional support, and continuous reflection. The paper concludes with practical recommendations for educators, curriculum developers, and policymakers